Differences in moral thinking among Tishreen University staff according to some variables A field study - Sbeira, Fouad (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The aim of this research was to identify the level of moral thinking among the employees of Tishreen University. In addition to the differences in the moral thinking of the employees in the faculties of Tishreen University. Abed al-Fattah's meta-scale 2001 was used to measure the level of moral thinking on the research sample. The descriptive method was used. The research hypothesized that there is a low level of moral intelligence among the employees in the faculties of Tishreen University. n addition, it was assumed that there were no statistically significant differences among the employees of these colleges according to some variables (gender, college type, years of experience). After testing the hypotheses, the following results were reached: 1- There is an above average level of ethical thinking among the employees at Tishreen University 2 - There are no statistically significant differences on the scale of moral thinking according to variables (sex, college, years of experience). The research proposes to pay attention to ethics and work to raise the level of this kind of thinking among university employees, and the need for a comprehensive and continuous mobilization on ethics in conjunction with the provision of the requirements and needs of employees in the university faculties in order to increase their motivation to work and succeed in it. بما يحقق زيادة دافعيتهم للعمل والنجاح فيه.